Parameter Neraca Hayati dan Pertumbuhan Populasi Kutu Putih Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) pada Dua Varietas Ubi Kayu - Nila Wardani; Aunu Rauf; Wayan Winasa; Sugeng Santoso (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
ABSTRACTThe life history and population growth parameters of mealybug Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) on two cassava varieties. The development, reproduction, and population growth parameters of the cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) on two cassava varieties were studied in laboratory. The varieties tested were UJ-5 with high cyanide content (>100 mg per kg) dan Adira-1 with low cyanide content (27.5 mg per kg). Our research revealed that P. manihoti performances were highly affected by cassava varieties. Incubation period of eggs of P. manihoti were 7.93 ± 0.09 and 8.33 ± 0.11 days, nymphal development periode 12.32±0.13 and 15.67 ± 0.13 days, respectively on UJ-5 and Adira-1. Fecundity averaged 386.37 ± 5.83 on UJ-5 and 318.67±2.81 eggs on Adira-1. Intrinsic rate of increase (rm) were 0.258 ± 0.001 on UJ-5 and 0.220 ± 0.001 on Adira-1. Mean generation time (T) on UJ-5 and Adira-1 were 22.795 ± 0.050 and 25.532 ± 0.047 days, repectively. Our findings showed that variety UJ-5 was more suitable for development and population growth of the cassava mealybug.